2020
DOI: 10.1002/pat.5130
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly materials produced by blown‐film extrusion as potential active food packaging

Abstract: Starch/polyester blends are potential substitutes for non‐degradable materials. Active food packaging was produced by the blown‐extrusion of starch/poly (butylene adipate‐co‐terephthalate) (PBAT) blends added to α‐tocopherol (α‐TOC). The films showed adequate stability and processability by the blown‐extrusion method and were converted into an essentially amorphous and homogeneous material. The transparency and water vapor permeability of the films increased with the addition of α‐TOC. The antioxidant interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…The degradation temperatures for thermoplastic starch (TPS) are registered around 320 °C. [ 2,19 ] Considering this, it was concluded that the thermal events of PVA overlapped with those of starch, and a single peak at approximately 372 °C (dTG— Figure ) was observed as a coalescence of the peaks corresponding to the degradation temperatures of starch and PVA.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The degradation temperatures for thermoplastic starch (TPS) are registered around 320 °C. [ 2,19 ] Considering this, it was concluded that the thermal events of PVA overlapped with those of starch, and a single peak at approximately 372 °C (dTG— Figure ) was observed as a coalescence of the peaks corresponding to the degradation temperatures of starch and PVA.…”
Section: Resultsmentioning
confidence: 98%
“…Considering the natural biodegradable materials, starch is particularly promising because of their availability, low cost, and abundance. [ 1,2 ] However, the poor mechanical properties and water sensitivity of the starch‐based materials remain a challenge to be overcome. The recent studies are focused in blended thermoplastic starch (TPS) with good performance biodegradable polymers, as PVA (poly(vinyl alcohol)), a synthetic polymer with excellent film forming ability, biodegradability, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…As an actual manufacturing process involves a blown extrusion process to produce films, this study investigated the effect of CNC by preparing a film using a simplified process (Figure 5, Table S3). 50 No noticeable difference was found during blown film processing with or without CNCs, and clean films without any impurities were obtained.…”
Section: Dispersion Of Cnc In Pbat/cnc Nanocompositesmentioning
confidence: 99%
“…Bio‐based and biodegradable materials represent an alternative to reduce the environmental impact of the non‐degradable packaging, with technical and economic feasibility, and a large potential for expansion (Galgano et al ., 2015; Bergel et al ., 2018). Starch is often used as a raw material to produce biodegradable packaging due to its renewable nature, low cost and abundance, also providing safe, complete and effective soil biodegradation (Yang et al ., 2013; Reis et al ., 2018; Lopes et al ., 2020; Simões et al ., 2020). However, the materials based only in starch have certain disadvantages such as inferior mechanical performance and sensitivity to moisture, which requires the inclusion of different components to improve the performance of the materials (Versino et al ., 2016; Travalini et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%